Characteristics of non-small cell lung cancer: Differences by sex and hormonal status in a Mexican population - Vianey Rodríguez-Lara; Laura Alejandra Ramírez-Tirado; Feliciano Barrón; Zyanya Lucía Zatarain-Barrón; Diana Flores-Estrada; Oscar Arrieta (Instituto Nacional de Salud Pública, 2019)
Objective. To analyze the differences in the clinico-pathological and molecular characteristics of non-small cell lung cancer (NSCLC) as well as the clinical outcome of patients by sex and hormonal status. Materials and methods. We performed a retrospective study among 1 104 NSCLC patients. Clinic-pathologic data was recorded and survival outcomes were compared between male and female sex patients, and further by pre and postmenopausal status in females. Results. Women were significantly more likely to be non-smokers (p<0.001), had higher frequency of wood-smoke exposure (p<0.001), EGFR-sensitizing mutations (p<0.001), had better performance status (p=0.020) and had a better overall survival (OS) compared to men (p=0.021). Differences were found also by hormonal status, postmenopausal women had a longer OS compared to premenopausal women (31.1 vs. 19.4 months p=0.046). Conclusion. Our results support the differences in lung cancer presentation by sex and also by hormonal status.